2016
DOI: 10.1038/lsa.2016.148
|View full text |Cite
|
Sign up to set email alerts
|

Light-driven micro-tool equipped with a syringe function

Abstract: Leveraging developments in microfabrication open new possibilities for optical manipulation. With the structural design freedom from three-dimensional printing capabilities of two-photon polymerization, we are starting to see the emergence of cleverly shaped ‘light robots’ or optically actuated micro-tools that closely resemble their macroscopic counterparts in function and sometimes even in form. In this work, we have fabricated a new type of light robot that is capable of loading and unloading cargo using ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(122 citation statements)
references
References 65 publications
0
122
0
Order By: Relevance
“…The challenge of deep body operations remains crucial to allow new emerging diagnostic procedures and targeted therapies, such as the identification and treatment of early‐stage cancers. Besides medicine, big advances on the propulsion and the navigation at the micron scale (Ahmed et al, ; Dai et al, ; Khalil et al, ; Kim et al, ; Kummer et al, ; Magdanz et al, ; Qiu et al, ; Solovev et al, ; Tottori et al, ; Villangca et al, ) open the way to neurosurgery operations by micromachines. Deep operations with microdevices, to be suitable for clinical use, need a submillimetre tracking system, providing localization in such heterogeneous and changing environments (Medina‐Sànchez & Schmidt, ).…”
Section: Resultsmentioning
confidence: 99%
“…The challenge of deep body operations remains crucial to allow new emerging diagnostic procedures and targeted therapies, such as the identification and treatment of early‐stage cancers. Besides medicine, big advances on the propulsion and the navigation at the micron scale (Ahmed et al, ; Dai et al, ; Khalil et al, ; Kim et al, ; Kummer et al, ; Magdanz et al, ; Qiu et al, ; Solovev et al, ; Tottori et al, ; Villangca et al, ) open the way to neurosurgery operations by micromachines. Deep operations with microdevices, to be suitable for clinical use, need a submillimetre tracking system, providing localization in such heterogeneous and changing environments (Medina‐Sànchez & Schmidt, ).…”
Section: Resultsmentioning
confidence: 99%
“…Light‐controllable microparticles can either have predefined shapes (e.g., microtools 3D‐printed in commercial negative photoresists such as IP‐L, IP‐G, Femtobond 4B, SCR‐701, NOA63 and SU‐8, or fabricated in SiO 2 through a double liftoff photolithographic process) or they can be based on light‐responsive materials (e.g., light‐sensitive polymers or liquid crystal elastomers …”
Section: Strategies For Improving Optical Trapping In Biological Samplesmentioning
confidence: 99%
“…The trap positions are displaced to scan a sample line‐by‐line and the spheres included in the probe are tracked in order to calculate the position of the tip, which allows a reconstruction of the sample topography. Our group has reported syringe‐like microrobots with a hollow body . These microrobots can be moved to a target site, loaded with cargo from their vicinity and then transported to a different site for unloading the cargo.…”
Section: Strategies For Improving Optical Trapping In Biological Samplesmentioning
confidence: 99%
“…For example in STED microscopy [12], it is necessary to have a "donut" shaped light pro le that suppresses uorescence excitation except at the center of the donut. The amount of refraction, re ection or absorption in an optically manipulated particle will also vary throughout the particle's extent, depending on its structure [25] or composition which can also be engineered [26]. Moreover, in laser materials processing, it has been shown that tailored patterned beams can control the melt ow out and kerf [7].…”
Section: Light Shaping and Light Distributionmentioning
confidence: 99%
“…Since the image gets saturated, the result is also presented at a lower camera gain. The easy switching from shaped beams makes matched ltering a convenient feature in a Holo-GPC setup and may give an extra "jolt" in optical manipulation applications [15], or higher intensities for secondary or non-linear e ects in multi-functional setups [26].…”
Section: Bringing Back Focusing Using Matched Filtering In Holo-gpcmentioning
confidence: 99%